Molecular epidemiology and pathology of spirorchiid infection in green sea turtles (Chelonia mydas). Issue 1 (April 2017) - Chapman, Phoebe A.; Owen, Helen; Flint, Mark; Soares Magalhães, Ricardo J.; Traub, Rebecca J.; Cribb, Thomas H.; Kyaw-Tanner, Myat T.; Mills, Paul C.
Abstract: Spirorchiid blood fluke infections affect endangered turtle populations globally, and are reported as a common cause of mortality in Queensland green sea turtles. Both the flukes and their ova are pathogenic and can contribute to the stranding or death of their host. Of particular interest are ova-associated brain lesions, which have been associated with host neurological deficits. Accurate estimations of disease frequency and the relative effect of infection relating to different spirorchiid species are made difficult by challenges in morphological identification of adults of some genera, and a lack of species-level identifying features for ova. A new specifically designed molecular assay was used to detect and identify cryptic spirorchiids and their ova in Queensland green sea turtle tissues collected from 2011 to 2014 in order to investigate epidemiology, tissue tropisms and pathology. Eight spirorchiid genotypes were detected in 14 distinct tissues, including multiple tissues for each. We found no evidence of a characteristic pathway of the eggs to the exterior; instead the results suggest that a high proportion of eggs become lost in dead-end tissues. The most common lesions observed were granulomas affecting most organs with varying severity, followed by arteritis and thrombi in the great vessels. The number of spirorchiid types detected increased with the presence and severity of granulomatous lesions. However, compared with other organs the brain showed relatively low levels of spirorchiid diversity. An inverse relationship between host age and spirorchiid diversity was evident for the liver and kidneys, but no such relationship was evident for other organs. Molecular data in this study, the first of its kind, provides the first species-level examination of spirorchiid ova and associated pathology, and paves the way for the future development of targeted ante-mortem diagnosis of spirorchiidiasis. Graphical abstract: Highlights: First species-level molecular study of spirorchiidiasis. Eight genotypes detected across fourteen tissue types. Species investigated in terms of tissue tropisms and pathology. Granulomas and arteritis/thrombosis most common lesions. Number of species present correlated with presence and severity of lesions.